The Influence of Static Pre-stretching on the Mechanical Ageing of Filled Silicone Rubbers for Dielectric Elastomer Applications - Shamsul, Zakaria; Yu, Liyun; Kofod, Guggi; Skov, Anne Ladegaard (Elsevier, 2015)
Abstract Dielectric elastomer (DE) pre-stretching is a key aspect of attaining better actuation performance, as it helps prevent electromechanical instability (EMI) and usually lowers the Young's modulus, thus leading to easier deformation. The pre-stretched DE is not only susceptible to a high risk of tearing and the formation of mechanical defects, but films with sustained and substantial strain may also experience mechanical degradation. In this study a long-term mechanical reliability study of DE is performed. Young's moduli, dielectric breakdown strengths and dielectric permittivities of commercial silica-reinforced silicone elastomers, with and without an additional 35 (35 phr) of titanium dioxide (TiO2), were investigated after being subjected to pre-stretching for various timespans at pre-stretches to strains of 60 and 120, respectively. The study shows that mechanical stability when pre-stretching is difficult to achieve with highly filled elastomers. However, despite the negative outlook for metal oxide-filled silicone elastomers, the study paves the way for reliable dielectric elastomers by indicating that simply post-curing silicone elastomers before use may increase reliability.